On-demand one-step synthesis of monodisperse functional polymeric microspheres with droplet microfluidics - Yu, Xu (Langmuir : the ACS journal of surfaces and colloids, 2015)
A simple and robust method for one-step synthesis of monodisperse functional polymeric microspheres was established by generation of reversed microemulsion droplets in aqueous phase inside microfluidic chips and controlled evaporation of the organic solvent. Using this method, water-soluble nanomaterials can be easily encapsulated into biodegradable Poly(D,L-lactic-co-glycolic acid) (PLGA) to form functional microspheres. By controlling the flow rate of microemulsion phase, PLGA polymeric microspheres with narrow size distribution and diameters in the range of ∼50-100 μm were obtained. As a demonstration of the versatility of the approach, high-quality fluorescent CdTe:Zn(2+) quantum dots (QDs) of various emission spectra, superparamagnetic Fe3O4 nanoparticles, and water-soluble carbon nanotubes (CNTs) were used to synthesize fluorescent PLGAQDs, magnetic PLGA@Fe3O4, and PLGA@CNTs polymeric microspheres, respectively. In order to show specific applications, the PLGA@Fe3O4 were modified with polydopamine (PDA), and then the silver nanoparticles grew on the surfaces of the PLGA@Fe3O4@PDA polymeric microspheres by reducting the Ag(+) to Ag(0). The as-prepared PLGA@Fe3O4@PDA-Ag microspheres showed a highly efficient catalytic reduction of the 4-nitrophenol, a highly toxic substance. The monodisperse uniform functional PLGA polymeric microspheres can potentially be critically important for multiple biomedical applications